Ammonium triggered the response mechanism of lysine crotonylome in tea plants - Sun, Jianhao (BMC Genomics, 2019)
BACKGROUND: Lysine crotonylation, as a novel evolutionarily conserved type of post-translational modifications, is ubiquitous and essential in cell biology. However, its functions in tea plants are largely unknown, and the full functions of lysine crotonylated proteins of tea plants in nitrogen absorption and assimilation remains unclear. Our study attempts to describe the global profiling of nonhistone lysine crotonylation in tea leaves and to explore how ammonium (NH(4)(+)) triggers the response mechanism of lysine crotonylome in tea plants. RESULTS: Here, we performed the global analysis of crotonylome in tea leaves under NH(4)(+) deficiency/resupply using high-resolution LC-MS/MS coupled with highly sensitive immune-antibody. A total of 2288 lysine crotonylation sites on 971 proteins were identified, of which contained in 15 types of crotonylated motifs. Most of crotonylated proteins were located in chloroplast (37%) and cytoplasm (33%). Compared with NH(4)(+) deficiency, 120 and 151 crotonylated proteins were significantly changed at 3 h and 3 days of NH(4)(+) resupply, respectively. Bioinformatics analysis showed that differentially expressed crotonylated proteins participated in diverse biological processes such as photosynthesis (PsbO, PsbP, PsbQ, Pbs27, PsaN, PsaF, FNR and ATPase), carbon fixation (rbcs, rbcl, TK, ALDO, PGK and PRK) and amino acid metabolism (SGAT, GGAT2, SHMT4 and GDC), suggesting that lysine crotonylation played important roles in these processes. Moreover, the protein-protein interaction analysis revealed that the interactions of identified crotonylated proteins diversely involved in photosynthesis, carbon fixation and amino acid metabolism. Interestingly, a large number of enzymes were crotonylated, such as Rubisco, TK, SGAT and GGAT, and their activities and crotonylation levels changed significantly by sensing ammonium, indicating a potential function of crotonylation in the regulation of enzyme activities. CONCLUSIONS: The results indicated that the crotonylated proteins had a profound influence on metabolic process of tea leaves in response to NH(4)(+) deficiency/resupply, which mainly involved in diverse aspects of primary metabolic processes by sensing NH(4)(+), especially in photosynthesis, carbon fixation and amino acid metabolism. The data might serve as important resources for exploring the roles of lysine crotonylation in N metabolism of tea plants. Data were available via ProteomeXchange with identifier PXD011610. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5716-z) contains supplementary material, which is available to authorized users.